Intertexting, une démarche participative de cocréation en appui des pratiques urbaines - Cedissia About; Émeline Bailly; Nathalie Blanc (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Based on reflections on citizen participation in neighborhoods, notions of the sensitive and environmental aesthetics, but also the role of art in citizen approaches, this article presents the Intertexting co-creation process as well as the first feedback of this new tool from different neighborhoods. The development of sensitive collective narratives opens up prospects for deployment in urban practices, from the neighborhood project to the urban project, with institutional actors and local actors.